2003
DOI: 10.1016/s0195-668x(02)00822-9
|View full text |Cite
|
Sign up to set email alerts
|

A randomised study of home-based electrical stimulation of the legs and conventional bicycle exercise training for patients with chronic heart failure

Abstract: FES produces beneficial changes in muscle performance and exercise capacity in patients with CHF. Within this study, the benefits were similar to those observed following bicycle training. FES could be offered to patients with heart failure as an alternative to bicycle training as part of a home-based rehabilitation programme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
94
0
4

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(107 citation statements)
references
References 32 publications
9
94
0
4
Order By: Relevance
“…NMES delivered at a frequency of 50 Hz and an amplitude chosen to induce muscle contractions at 25-30% of maximal voluntary contraction induced significant increases in the strength and cross-sectional area of the thigh muscles in CHF patients awaiting heart transplantation [38]. Subsequently, additional studies have confirmed the benefits of NMES in CHF patients [39,40].…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 94%
“…NMES delivered at a frequency of 50 Hz and an amplitude chosen to induce muscle contractions at 25-30% of maximal voluntary contraction induced significant increases in the strength and cross-sectional area of the thigh muscles in CHF patients awaiting heart transplantation [38]. Subsequently, additional studies have confirmed the benefits of NMES in CHF patients [39,40].…”
Section: Transcutaneous Neuromuscular Electrical Stimulationmentioning
confidence: 94%
“…After a series of NMES treatment sessions, increased muscle endurance was also noted in patients with CHF [12]. The strength of stimulated muscles increased by approx.…”
Section: Application Of Nmes In Patients With Chronic Heart Failurementioning
confidence: 89%
“…The observed improvement of muscular strength applies to both isokinetic [14,21,22] and isometric [21] contractions. It seems that these changes are caused by the increase in aerobic enzyme activity of skeletal muscles, which, in turn, leads to an increased oxidative capacity [9,[12][13][14]18]. Moreover, it was observed through the biopsy procedure that due to the application of NMES, an increase in type I muscle fibers occurs, which proves the evident recalibration of the stimulated muscles in the direction of aerobic metabolism and endurance training [13].…”
Section: Application Of Nmes In Patients With Chronic Heart Failurementioning
confidence: 95%
See 2 more Smart Citations